1997
DOI: 10.1016/s0969-2126(97)00281-5
|View full text |Cite
|
Sign up to set email alerts
|

Structures of class pi glutathione S-transferase from human placenta in complex with substrate, transition-state analogue and inhibitor

Abstract: In the structure of the GST-glutathione complex, two conserved water molecules are observed, one of which hydrogen bonds directly to the sulphur atom of glutathione and the other forms hydrogen bonds with residues around the glutathione-binding site. These water molecules are absent from the structure of the Meisenheimer complex bound to GST, implicating that deprotonation of the cysteine occurs during formation of the ternary complex which involves expulsion of the inner bound water molecule. The comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 35 publications
5
57
0
Order By: Relevance
“…Tyr 152 , together with Arg 14 , Glu 96 , and two water molecules bound at the bottom of the catalytic cleft (Fig. 1C), is thought to form the hydrogen bonding network involved in the binding of GSH, as reported in the Pi class GSTs (40). The partial decrease in both PGDS and GST activities of Y152F (Fig.…”
mentioning
confidence: 53%
“…Tyr 152 , together with Arg 14 , Glu 96 , and two water molecules bound at the bottom of the catalytic cleft (Fig. 1C), is thought to form the hydrogen bonding network involved in the binding of GSH, as reported in the Pi class GSTs (40). The partial decrease in both PGDS and GST activities of Y152F (Fig.…”
mentioning
confidence: 53%
“…Recent crystal structures of the human class pi GST have provided detail of a further binding site located in the hydrophobic cavity between the secondary structural elements β2 and A1. One molecule of N-(2-hydroxethyl)piperazine-N′-2-ethanesulphonic acid (Hepes) and N-morpholino-ethansulphonic acid (Mes) has been shown to bind per GST subunit [29,39]. Competitive binding studies between BSP and ANS, and BSP and Hepes in human GST A1-1 indicate that BSP most probably competes for the Hepes binding site.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first structure in which ligand binding outside of the G-and H-sites was demonstrated in a cytosolic GST. Several structures of the human pi-class GST feature binding of the buffersubstances MES or HEPES at a site adjacent to W28, located at the N-terminal end of strand β2 (Ji et al 1997;Oakley et al 1997b;Prade et al 1997) (Figure 8c, d). Later studies demonstrated binding of ligands in various binding sites: Sulfasalazine (a sulfa-drug), cibacron blue (a sulfonated triazine dye) and bromosulfophthalein (used in liver function tests) bind in the H-site (Oakley et al 1999).…”
Section: Gsts As Ligandinsmentioning
confidence: 99%